Evaluation of Visitor Responses to Lake Sipin Tourism Services - Ramadhan, Gusti; Sukhragchaa, Amarjargal; Sarkar, Tushar (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: The aim of this research is to explore visitors' experiences and perceptions of Lake Sipin water tourism in Jambi and identify the factors that influence their satisfaction, with the hope of providing deeper insight into the potential and challenges in managing similar natural tourism destinations in the future. Methodology: This research method adopts a naturalistic qualitative approach with data collection techniques in the form of interviews and documentation. The research population was tourist visitors who visited Lake Sipin in Jambi, with a sample selected purposively to cover diversity of visitor characteristics. The data collected was analyzed thematically to identify themes that emerged from the interview transcriptions and documentary material. Main Findings: The main results of the research show that visitors' experiences of Lake Sipin water tourism in Jambi are influenced by several key factors, including natural beauty, interaction with the local environment, quality of facilities, and cultural diversity. Visitors stated that environmental cleanliness and safety were their main concerns, while interaction with local residents and participation in local cultural activities added value to their tourism experience. Novelty/Originality of this study: The novelty of this research lies in its in-depth approach to the visitor experience at Lake Sipin, which not only explores the physical aspects of the destination, but also explores social, cultural and environmental interactions in understanding the dynamics of water tourism in Jambi and a valuable contribution in enriching the literature on natural tourism in Indonesia